2015
DOI: 10.1589/jpts.27.1655
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chest resistance exercise and chest expansion exercise on stroke patients’ respiratory function and trunk control ability

Abstract: [Purpose] The purpose of this study was to examine the efficiency of chest resistance and chest expansion exercises for improving respiratory function and trunk control ability in patients with stroke. [Subjects] Forty patients with stroke were randomly allocated into a chest resistance exercise group (CREG, n = 20) and a chest expansion exercise group (CEEG, n = 20). [Methods] CREG patients underwent chest resistance exercises, and diaphragmatic resistance exercises by way of the proprioceptive neuromuscular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 17 publications
2
30
0
Order By: Relevance
“…These findings are in the same direction study by Seo et al (2017) [40] who reported the respiratory exercise has positive impacts on stroke patients' respiratory muscles during the diaphragm breathing exercise. Also similar to Song and Park (2015) [41] reported that chest resistance and expansion exercises were helpful for improving pulmonary function in stroke patients.…”
Section: Discussionsupporting
confidence: 65%
“…These findings are in the same direction study by Seo et al (2017) [40] who reported the respiratory exercise has positive impacts on stroke patients' respiratory muscles during the diaphragm breathing exercise. Also similar to Song and Park (2015) [41] reported that chest resistance and expansion exercises were helpful for improving pulmonary function in stroke patients.…”
Section: Discussionsupporting
confidence: 65%
“…A study has confirmed that breathing training can significantly increase muscle strength and trunk coordination in stroke patients with hemiplegia and also improve respiratory function [35,36]. It has been reported that respiratory muscle strength training or complex breathing exercises can effectively improve the stability of the trunk posture of stroke patients [37], and it has been proven that resistance training of the thoracic cage can significantly improve respiratory function and the trunk control ability of stroke patients [38]. Nelson proposed that breathing is the foundation of core stability, and core stability is the foundation of movement [39].…”
Section: Discussionmentioning
confidence: 97%
“…Patients with cerebral apoplexy generally have abnormal breathing, which is often manifested as decreased exhalation ability [11]. Because of all these factors, proper breathing exercises, especially exhalation exercises, are necessary in patients with stroke [12].…”
Section: Introductionmentioning
confidence: 99%
“…[35] [36]. It has been reported that respiratory muscle strength training or complex breathing exercises can effectively improve the stability of the trunk posture of stroke patients [37] and it has been proven that resistance training of the thoracic cage can significantly improve respiratory function and the trunk control ability of stroke patients [38]. Nelson proposed that breathing is the foundation of core stability, and core stability is the foundation of movement [39].…”
Section: Discussionmentioning
confidence: 99%